Відновлення деталей напиленням алюмінієвих електродугових покриттів з наступною їх плазмоелектролітною обробкою - Шмирко, Віктор; Студент, Михайло; Клапків, Михайло (КІНПАТРІ ЛТД, 2013)
The method recovery geometric dimensions of worn parts was developed. It is electric arc spraying aluminum alloys produced by surface followed plasma electrolytic oxidation surface finish. These metaloxide ceramic coating with high wear- and corrosion resistance.
Repair parts aluminium arc spray coating with their subsequent plasma electrolytic oxidation rendered